2019
DOI: 10.1186/s12879-019-3792-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in norovirus genotype diversity in gastroenteritis outbreaks in Alberta, Canada: 2012–2018

Abstract: Background The emergence of norovirus genotype GII.4 variants has been associated with gastroenteritis pandemics worldwide, prompting molecular surveillance for early detection of novel strains. In this study, we aimed to analyze the outbreak activity of norovirus and characterize the norovirus strains circulating in Alberta between July 2012 and February 2018. Methods Stool samples from gastroenteritis outbreaks in Alberta were tested for norovirus at the Provincial La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Previous studies have demonstrated that the GII virus was frequently detected compared with the GI virus from the NoV infection [2831], which was consistent with our results. In contrast, both the GI and GII virus genomes were detected in environmental water at equivalent frequencies using real-time RT-PCR [32, 33] possibly due to the difference in stability between the GI and GII capsid proteins [34].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that the GII virus was frequently detected compared with the GI virus from the NoV infection [2831], which was consistent with our results. In contrast, both the GI and GII virus genomes were detected in environmental water at equivalent frequencies using real-time RT-PCR [32, 33] possibly due to the difference in stability between the GI and GII capsid proteins [34].…”
Section: Discussionsupporting
confidence: 93%
“…The genogroups are subdivided in >30 genotypes. The predominant strain causing both outbreaks and sporadic cases of gastroenteritis is GII.4 [7,8]. Novel variants of GII.4 emerge periodically, spread rapidly across the globe, and cause pandemics [9].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple GII.4 viruses were associated with epidemics during the 2000s. Since 2010, a single variant, GII.4 Sydney, has been the predominant virus ( 2 5 ). A recombinant GII.P16-GII.4 Sydney strain emerged in July 2015 and caused 72% of the outbreaks in the winter of 2017–18 ( 2 ).…”
mentioning
confidence: 99%
“…Since 2010, a single variant, GII.4 Sydney, has been the predominant virus ( 2 5 ). A recombinant GII.P16-GII.4 Sydney strain emerged in July 2015 and caused 72% of the outbreaks in the winter of 2017–18 ( 2 ). A small wave of activity with the Kawasaki GII.17 and GII.P16-GII.2 strains was seen during 2016–2017, but they did not predominate.…”
mentioning
confidence: 99%